Strategic Implementation And Cost Justification Of Advanced Manufacturing Technology - Low, Kevin Lock Teng (2003)
The manufacturing environment has changed significantly since the turn of the century, especially with respect to the machinery and equipment used to manufacture products. As competition becomes stronger, companies turn to new and more efficient machines and technologies to help them produce a lower cost and good quality product. At no time in the last twenty years has competition been stronger, because manufacturers must not only compete with domestic companies, but also with foreign, often with load of funds or goverment-supported companies.